2008
DOI: 10.4067/s0717-95022008000300016
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Mesiodistal and Bucolingual Tooth Dimensions in Chilean People

Abstract: SUMMARY:The study investigates the presence of sexual dimorphism in the size of the permanent teeth among Chilean individuals. Mesiodistal and bucolingual diameters were measured in the teeth of 150 patients between 18 and 24 years old, 67 males and 83 females (excluded were third molars and pieces with large cavities and fillings). The largest were found in males; the differences in mean bucolingual diameters with p<0.05 were observed in pieces 1.1, 1.2, 1.3, 1.6, 1.7, 2.6, 3.3, 4.1, 4.2, and 4.5; and with p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Sexual dimorphism, therefore, has a vital significance in forensic odontology and medicine. 20 Teeth are useful to differentiate gender by calibrating their buccolingual and mesiodistal dimensions. Use of teeth to determine gender have an essential role in young people where the skeletal secondary sexual features like breast, hip broadening and moustaches have not yet developed.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism, therefore, has a vital significance in forensic odontology and medicine. 20 Teeth are useful to differentiate gender by calibrating their buccolingual and mesiodistal dimensions. Use of teeth to determine gender have an essential role in young people where the skeletal secondary sexual features like breast, hip broadening and moustaches have not yet developed.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the teeth is of great importance not only to indicate the different activities related to the occlusion or to determine the frequency of dental–tooth anomalies applied to the orthodontic treatment, but also to establish sexual dimorphism. [ 9 ] This, therefore, will have great significance in forensic odontology. Because of this, the knowledge of coronary dimensions for the identification of sex when skeletons are found becomes relevant, especially when anatomical parameters are not reliable for identifying a particular subject.…”
Section: Discussionmentioning
confidence: 99%
“…Ling JY's study on the southern chinese population consisting of 459 patient's states that male had larger mesiodistal dimensions in incisors, canines and premolars [7]. Suazo's study on the Chilean population of 150 patients concluded Chilean males had greater buccolingual dimensions on comparing canines and premolars [8]. A study on the Nepalese population by acharya [9] showed that buccolingual dimension maxillary molar showed significant statistically significant differences between sexes with males showing larger dimensions.…”
Section: Discussionmentioning
confidence: 99%